If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -4 + 5x = -36 Reorder the terms: -4 + -1x + 5x = -36 Combine like terms: -1x + 5x = 4x -4 + 4x = -36 Solving -4 + 4x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4x = -36 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = -36 + 4 4x = -36 + 4 Combine like terms: -36 + 4 = -32 4x = -32 Divide each side by '4'. x = -8 Simplifying x = -8
| 0.2+0.25=0.45x-0.2 | | -4(6n-6)+3n= | | x(3x+14)+11=0 | | 8+15-8= | | 35x+86=123 | | 5(z-5)+7z-4= | | 5+.75h=10 | | 4(x+2)=6(x-1)-2 | | x^4-8x^3+14x^2-4x-3=0 | | 3.4x=2.4x+5.0 | | -14=-7w | | 2(2p-3)-18= | | n-14=8n | | 0=1.77x+187 | | 4x^2-19+12=0 | | 9(3a+1)a=2 | | 2b-5-9b-3= | | (x+3)2=64 | | 24-1/2=0 | | 6x+10=-68-7x | | 0,4(2x-7)+1,2(3x+0,7)=1,6x | | 04(2x-7)+1,2(3x+0,7)=1,6x | | 12x-24=-36 | | z+4=-10 | | 12+8n=20 | | 8x^3+14x^2-4x= | | 9x-52=5x-8 | | -9(5x+6)+6= | | 7+6(u-6)+5u=2(5u+12) | | -2n+4(5-n)=2(2n+30) | | 2z+1/4=3/4 | | 5+2n=7-4n |